Development of Fabry Perot antenna inspired by patch-type frequency selective surface (FSS) for X band communication - Elmi, Mohamed Ali (2015)
Fabry Perot antenna with Frequency Selective Surface (FSS) has been presented and analyzed in this project. Fabry perot antenna has numerous applications like satellites communication, radar, telecommunications and broadcasting and sensor systems. The proposed antenna structure consist of microtrip patch antenna which is the primary source of radiation, ground plane which acts as a totally reflective surface, and Partially Reflective Surface (PRS) with a distance of half wavelength in between them. The PRS is a dielectric material with a periodically spaced square patches of copper printed on it. The main advantage of the presented structure is the simultaneous enhancement of both gain and bandwidth. The primary desired design goal is to achieve high gain with a low profile antenna. By increasing the reflection coefficient of PRS, directivity will be improved. The size and the shape of the printed material and the distance of PRS from the source have also a numerous effect on the gain and bandwidth. The antenna was designed to operate at a frequency of around 10 GHz. This proposed structure increased the gain from 9.2 dB up to 14.65 dB and bandwidth improvement of about 1%. To validate the theoretical analysis, the antenna has been designed and simulated using the commercially available software of CST studio.